Heat transfer models for two-component media with interfacial jump. Issue 2 (25th January 2017) - Gruais, I.; Poliševski, D.
Abstract : The paper deals with the asymptotic behaviour of the heat transfer in a bounded domain having an -periodic structure formed by two interwoven components separated by an interface on which the heat flux is continuous and the temperature subjects to a first-order jump condition. We study the cases when the orders of magnitude with respect to of the ratio between the two conductivities and of the jump transmission coefficient are, respectively, and, with and . We derive the macroscopic laws and the effective coefficients obtained by the two-scale convergence technique of the homogenization theory.